Balancing the Tides : Marine Practices in American S?moa - Poblete, JoAnna, 1974- (Book collections on Project MUSE., 2020)
"Balancing the Tides highlights the influence of marine practices and policies in the unincorporated territory of American Sāmoa on the local indigenous group, the American fishing industry, international seafood consumption, U.S. environmental programs, as well as global ecological and native concerns. Poblete explains how U.S. federal fishing programs in the post-World War II period encouraged labor based out of American Sāmoa to catch and can one-third of all tuna for United States consumption until 2009. Labeled "Made in the USA," this commodity was sometimes caught by non-U.S. regulated ships, produced under labor standards far below continental U.S. minimum wage and maximum work hours, entered U.S. jurisdiction tax free, and was sometimes caught by non-U.S. regulated ships. The second half of the book explores the tensions between indigenous and U.S. federal government environmental goals and ecology programs. Whether creating the largest National Marine Sanctuary under U.S. jurisdiction or collecting basic data on local fishing, initiatives that balanced western-based and native expectations for respectful community relationships and appropriate government programs fared better than those that did not acknowledge the positionality of all groups involved. Balancing the Tides demonstrates how western-style economics, policymaking, and knowledge building imposed by the U.S. federal government have been infused into the daily lives of American Sāmoans. American colonial efforts to protect natural resources intersect with indigenous insistence on adhering to customary principles of respect, reciprocity, and native rights in complicated ways. Experiences and lessons learned from these case studies provide insight into other tensions between colonial governments and indigenous peoples engaging in environmental and marine-based policymaking across the Pacific and the globe. Poblete's study connects the U.S.-American Sāmoa colonial relationship to global overfishing, world consumption patterns, the for-profit fishing industry, international environmental movements and studies, as well as native experiences and indigenous rights"--